Law and Ethics of Installing CCTV in Private Places: A Privacy Protection Perspective in the Digital World - Naufal Wala, Gevan (Siber International Journal of Advanced Law (SIJAL), 2025)
This study examines the legal and ethical aspects of installing CCTV in private spaces, focusing on privacy protection in the digital age. Using a qualitative descriptive-analytical approach, data were collected through interviews with legal experts, digital ethics scholars, and security practitioners, as well as a review of relevant laws and literature. The findings reveal a significant increase in CCTV installations driven by security concerns, yet highlight serious legal and ethical dilemmas. Indonesia’s current legal framework, including the Electronic Information and Transactions Law and the Personal Data Protection Law, recognizes the right to privacy but lacks specific regulations governing the installation of CCTV in private areas. Ethically, while surveillance in semi-public areas within private property may be acceptable with clear notification, installation in sensitive private spaces such as bedrooms and bathrooms constitutes a serious breach of privacy and human dignity. The study underscores the need for more detailed regulations, public education on privacy rights, and a balanced approach that safeguards both security and personal privacy. Strengthening legal mechanisms and ethical awareness is crucial to prevent misuse of surveillance technology in private settings.